Recent Developments in Bacterial Nanocellulose Production and its Biomedical Applications - Chandana A.; Mallick S.P.; Dikshit P.K.; Singh B.N.; Sahi A.K. (My University, 2025)
Cellulose, the most abundant polysaccharide on earth, can be obtained from various sources including the cell wall of plants and woods, bacteria, algae, and tunicates. However, the cellulose obtained from bacteria known as bacterial cellulose or bacterial nanocellulose (BC) has gained major popularity due to its simple production process, non–toxicity, high purity, and biocompatibility. Furthermore, the BC holds distinct properties like higher crystallinity, larger surface area, high porosity, great water holding capacity, and enhanced tensile strength. These unique features of BC further widen its application in several areas including drug delivery, tissue engineering, wound dressing, etc. The present review summarizes the recent developments in BC production and its biomedical applications. Firstly, the microorganisms involved, various medium compositions used and the methods adopted for BC production are discussed, and then reactors used for industrial production of BC are introduced. Subsequently, the applications of BC in tissue engineering, drug delivery system, and pharmaceutical & medical sectors are discussed in detail. Finally, the future perspective of BC in biomedical applications is discussed in brief. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.